Determining the Grounds for Conducting Examination through the Prism of Investigative Practice - Ya. Yu. Koniushenko (Law and Safety)
The problems of determining the grounds for such an investigative (search) action as an examination have been clarified. The purpose of the article is to determine the grounds for conducting an examination, as well as to distinguish problematic aspects that arise in the investigative practice at the initial stage of conducting an examination.